Utilização de mensagens criptografadas no ensino de matrizes - Oliveira, Reinaldo Donizete de (2013)
The present work aims at showing the development and implementation of a Didactic Engineering on the use of encrypted messages in teaching matrices to students who are attending the second high school year at Esmeralda Soares Ferraz School in the City of Ourinhos-SP. This work begins with a question related to the discouragement and apathy of students in studying mathematics and suggests, taking the teaching of matrices through encrypted messages by transposition of letters, a different approach from those commonly applied, through which, the student eager to solve them, will get engaged and interested in learning, in a simple way, the concepts of matrices and transposed matrices, being protagonist of his/her search for knowledge.